Social psychology a space for observation and practical application - maklouf, boumedian (Journal of Social Sciences and Humanities, 2019)
The family structure forms the center of social consciousness and civilization. It transmits heritage among generations, which is the source of customs and traditions, customs, rules of conduct and public morals. It is the pillar of religion and the commandment for its rituals. It is credited with performing the most important social function,). Sociologically, socialization within the overall social context is "an evolutionary and cumulative pattern of rules and values through which the child can assimilate the various behaviors, norms and patterns of thought of his socio-culturelle" and take the family as a central structural framework. And skills at a value level, as a cultural capital (Le capital culture). In this sense, upbringing is a family function whose main core is the development of social roles (Les rôles sociaux). From a value perspective, the méthode of social upbringing at the family level as an educational and religious institution establishes social capital. It contributes to the implantation of culture and elevates it to the level of value. Interaction, communication and integration (les normes) The sociological value of the child, the child acquires its educational value mainly by the family members, and from a sociological perspective, Erikson's theory of the stages of psychological and social development emphasizes the close relationship between the individual and his family. The family is a value that educates its children on the principles and ideals of respect and appreciation The Time, commitment, and rooting at the level of the patterns that you will belong to.-